Optimalisasi Deteksi Dini Gangguan Tumbuh Kembang dan Pencegahan Stunting Melalui Pemeriksaan Balita dan Ibu Hamil di Posyandu Kecamatan Kawalu - Pangripta, Genta; Miftahul Falah; Handayani, Hani; Setiawan, Asep; Abdurahman, Imam; Zalianti, Nova; Fauziah, Hilma Fiza; Yastuti, Meylani Indri; Nuryadin, Yadin; Martanti, Nurmala Nurani; Nurani, Ai Yasri; Kurniawati, Ade; Imaniar, Melsa Sagita; Nugraha, Budy; Yulita, Feni (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
This community service initiative aimed to enhance early detection of growth disorders in toddlers and maternal health at eight community health posts (Posyandu) in Kawalu District. The topic was selected based on the high prevalence of stunting and the need for monitoring maternal health in the area. Methods included interactive health education, anthropometric measurements (height and weight of toddlers) according to WHO standards, and health assessments of pregnant women. Of the 83 toddlers measured, 27.7% were classified as normal, 48.2% as stunted, and 24.1% as severely stunted. These findings indicate a persistently high burden of chronic malnutrition. Among pregnant women, most reported dizziness, nausea, and vomiting; while the majority regularly consumed iron tablets (Fe), tetanus toxoid (TT) immunization coverage remained low. The results of this service underscore the importance of ongoing education, growth monitoring, and improved antenatal services to reduce stunting prevalence and enhance maternal health.